2016
DOI: 10.3171/2015.2.jns141993
|View full text |Cite
|
Sign up to set email alerts
|

Time-delayed contrast-enhanced MRI improves detection of brain metastases and apparent treatment volumes

Abstract: B rain metastases (BMs) are the most common intracranial tumors in adults, occurring in 20%-40% of cancer patients. 26 Their incidence has been increasing due to both prolonged systemic control and improved detection, making BMs a growing cause of mortality and morbidity.14,31 Magnetic resonance imaging is currently the standard of care for the diagnosis of BMs because its sensitivity is superior to CT,22,32 and refinements in MRI techniques allow the modality to detect metastases that are not seen with routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…To date, the available studies have used linear structured Gd-DTPA and there are no studies that have used circular structured gadobutrol. Consistent with the earlier studies that have reported detection of lesions less than 5 mm (5,18), this study also reports detection of an additional six lesions in the 7-and 10-min delay groups compared with the 3-min group. All the additionally detected lesions had diameters of less than 5 mm.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To date, the available studies have used linear structured Gd-DTPA and there are no studies that have used circular structured gadobutrol. Consistent with the earlier studies that have reported detection of lesions less than 5 mm (5,18), this study also reports detection of an additional six lesions in the 7-and 10-min delay groups compared with the 3-min group. All the additionally detected lesions had diameters of less than 5 mm.…”
Section: Discussionsupporting
confidence: 91%
“…The diagnosis was mainly based on typical imaging manifestations and clinical follow-up. Second, unlike other studies (5,18), the delay time was up to 10 minutes, and this was mainly because well-known Chinese hospitals do not allow for longer examination time due to excess clinical work. Finally, the small sample size of this study does not allow for generalization of the findings.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For instance, a time delay of 15 minutes after contrast injection results in at least one additional lesion being detected in 43% of patients (Kushnirsky et al, 2016). Resultant radiation tumor treatment volumes also increase with time delay.…”
Section: Enhancing Detection Of Small Metastasesmentioning
confidence: 99%